Etika Berpolitik: Pandangan Islam terhadap Black Campaign dalam Berdemokrasi - Nabila Rizkia; Syahidin Syahidin (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Black campaigning has become an increasingly troubling issue in the modern political context, including in general elections. The Islamic view of this phenomenon confirms that such actions fall into the category of despicable behavior that must be avoided. In the study of fikih siyasah and Islamic religious teachings, black campaigns are considered to involve actions that are contrary to the moral and ethical principles taught by religion. The practice of black campaigning can cause conflict, division, and distrust in the community towards the ruling government. The use of sensitive issues such as SARA can also worsen the atmosphere and damage national unity. This research uses a literature study that aims to look at the Islamic view of black campaigns, as well as their impact on society and the democratic process.